Focal Therapy and Prostate Cancer. Issue 4 (October 2013) - Lazzeri, Massimo; Losa, Andrea; Buffi, Nicolòmaria; Lughezzani, Giovanni; Fossati, Nicola; Abrate, Alberto; Larcher, Alessandro; Lista, Giuliana; Mistretta, Alessandro; Guazzoni, Giorgio
The International Task Force on Prostate Cancer defines focal therapy (FT) for prostate cancer (PCa) as the therapy that "selectively ablates known disease and preserves existing functions, with the overall objective of minimizing lifetime morbidity without compromising life expectancy". FT for the treatment of PCa has been called the "male lumpectomy", an analogue to women's breast lumpectomy for the treatment of breast cancer. Radical prostatectomy continues to be the most frequently performed treatment for localized PCa, as anatomic knowledge and several technical advances, i.e. the introduction of robotic assisted surgery, have led to successful oncological outcome and lower rates of post-treatment morbidity. However, a proportion of patients still experiences a no negligible sexual, urinary, and bowel morbidity. Although the rationale of active surveillance for low-risk PCa (PSA <10 ng/mL, Gleason grade 6 or less, and clinical stage T1c-T2a) is sound, only few of newly diagnosed patients elect this approach. Thus, in the recent years the concept of a "subtotal therapy" gained the interest of some urological schools. The aim of this paper is to review the existing literature in order to provide the status of art on FT for PCa. The manuscript will focus on the characteristics of the target population, on the pre-operative evaluation to localise disease, as well as on perioperative, functional, and disease-control following focal therapy. L'International Task Force on Prostate Cancer definisce la terapia focale (TF) per il carcinoma prostatico (CP) una terapia che selettivamente distrugge la neoplasia precedentemente individuata e preserva le funzioni dell'organo, con l'obiettivo di minimizzare la morbilità senza compromettere la radicalità oncologica. La TF per il CP è stata paragonata alla quadrantectomia per il tumore della mammella. Sebbene, grazie ad una maggiore conoscenza anatomica e all'innovazione tecnologica, rappresentata in primis all'introduzione della piattaforma robotica, la prostatectomia radicale continua ad essere il trattamento radicale più diffuso per la cura del CP localizzato, l'impatto delle complicazioni urinarie, sessuali ed intestinali sulla qualità di vita non è trascurabile. La sorveglianza attiva è stata considerata un'alternativa ai trattamenti radicali per pazienti con basso rischio (PSA <10 ng/mL, Gleason score 6, stadio clinico T1c-T2a). Sfortunatamente una significativa percentuale di pazienti in sorveglianza attiva viene successivamente avviata a terapia radicale sia per riclassificazione bioptica o per motivi psicologici. Negli ultimi anni ha quindi preso campo la possibilità di una terapia sub totale o focale. L'obiettivo di questo lavoro è quello di rivedere la letteratura recente sul tema cercando di identificare quali siano le caratteristiche del paziente candidabile, gli strumenti impiegati per l'esatta localizzazione della neoplasia, le principali tecniche usate e le strategie di follow-up.